PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN PEMERKOSAAN BERDASARKAN UU NOMOR 17 TAHUN 2016 TENTANG PERUBAHAN KEDUA ATAS UU NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Nabilla Karnia Soraya; Diah Ratu Sari (JOURNAL OF LAW AND NATION, 2023)
Legal protection for children, especially those who have experienced sexual violence often occurs lately, and the most severe crime of sexual violence that is currently not only done by adults but also by children. Also carried out by children. With the formulation of the problem: (1) What are the legal protection efforts for children who are victims of the crime of rape in the legislation? (2) How is the implementation of legal protection for children who are victims of rape in Indonesia? (3) What is the expected legal protection for child victims of rape in the future? By using a normative legal research method, the results obtained (1) In accordance with the applicable law. Legal protection for child victims of rape states that a child who is a victim of a crime has the right to receive rehabilitation from the government both physically and mentally, spiritually and socially, in addition to Therefore, his privacy must be protected, his good name is protected and maintained, his safety as a witness to the victim is the responsibility of the government, and the child who is the victim has the right to always know the progress of the case he is facing. (2) There are still some law enforcement officers who do not treat the victims in this case with a female perspective. The handling of sexual violence cases is also too long because they have to follow legal procedures which make victims reluctant to face the law, which is a very tiring process. (3) Coordination with the police must be carried out, so that the police immediately seek assistance from the institution concerned when they receive a report of an act of rape. Based on the research conducted, the authors suggest that the provisions regarding compensation for victims should also be included in the legislation in force in Indonesia, so that in cases of criminal acts of sexual violence, the judge not only imposes criminal sanctions on the perpetrators, but also decides on the compensation obtained. By the victim. Compensation given to victims is not only to compensate for the losses they have suffered but also as a manifestation of the highest legal ideals in Indonesia, namely Pancasila, the 5th precept of justice for all Indonesian people.